Early age tensile creep of high performance concrete containing mineral admixtures: Experiments and modeling. (10th February 2019) - Gu, Chunping; Wang, Yicong; Gao, Fan; Yang, Yang; Ni, Tongyuan; Liu, Jintao; Lou, Xiaotian; Chen, Jin
Highlights: An early age tensile creep test system was designed and presented in the paper. The effect of mineral admixtures on the early age tensile creep of HPC was studied. ZC model was proposed to predict the early age tensile creep of HPC containing mineral admixtures. The applicability of proposed model was verified with data from literatures. Abstract: In the paper, the early age tensile creep behavior of high performance concrete (HPC) containing mineral admixtures was experimentally investigated. The results showed that, when the loading age was at 1 d and 2 d, the addition of fly ash (FA) increased the early age specific tensile creep of HPC, while blast furnace slag (BFS) showed an opposite effect. When the loading age was later than 3 d, the early age specific tensile creep of HPC was not obviously influenced by FA and BFS. Based on the experimental results, a rheology-based model (named as "ZC", initials for the word "Self-developed" in Chinese) was proposed to predict the early age tensile creep of HPC with mineral admixtures. The ZC model was validated with other experimental results, and the prediction results agreed well with the experimental data. Moreover, the limitations and further improvements on the proposed model were also discussed in the paper.